Sexual assertiveness, self-efficacy, and sexual risk behaviors in adolescents: A literatura review - Corral-Gil, Guadalupe de Jesús (2022)
Objective: To identify the available scientific literature on sexual assertiveness, self-efficacy and risky sexual behavior in adolescents. Method: Integrative review, in order to clarify the following question: What is the relationship between sexual assertiveness, self-efficacy and sexual risk behaviors in adolescents? The search was performed in the Web Of Science (WOS), EBSCOhost¸Scopus and GoogleScholar databases. Main results: 6 studies were analyzed, and their main findings are that self-efficacy influences CSR; condom use is not associated with self-efficacy, and self-efficacy is positively related to sexual debut; self-efficacy and self-efficacy in condom use is associated with saying no to engaging in sexual activity; self-efficacy was found to be a protective factor against health risk behaviors and CSR. General conclusion: Sexual assertiveness and self-efficacy may be factors that contribute to the development of skills to prevent CSR, behaviors that in recent years have caused various health problems in adolescents, who tend to be more prone to risky practices, this perhaps due to what the process of adolescence as such entails.